Significant cases in juvenile justice - Hemmens, Craig (Criminal justice case briefs, 2004)
Introduction/history of the juvenile court -- Juvenile curfew -- Juveniles and the police -- Entry into the court system -- Detention -- Waiver to criminal court -- Adjudication in juvenile court -- Disposition -- Conditions of confinement -- The release decision.